2011
DOI: 10.1007/s11145-011-9300-4
|View full text |Cite
|
Sign up to set email alerts
|

Speech production deficits in early readers: predictors of risk

Abstract: Speech problems and reading disorders are linked, suggesting that speech problems may potentially be an early marker of later difficulty in associating graphemes with phonemes. Current norms suggest that complete mastery of the production of the consonant phonemes in English occurs in most children at around 6–7 years. Many children enter formal schooling (kindergarten) around 5 years of age with near-adult levels of speech production. Given that previous research has shown that speech production abilities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 66 publications
1
17
0
3
Order By: Relevance
“…22 In contrast, the onset of stuttering is associated with higher, rather than lower, maternal education. 6 Even in population studies with both sufficient sample size and breadth to build comprehensive risk models, much of the preschool variance in all three disorders remains unexplained.…”
Section: Sources and Selection Criteriamentioning
confidence: 99%
“…22 In contrast, the onset of stuttering is associated with higher, rather than lower, maternal education. 6 Even in population studies with both sufficient sample size and breadth to build comprehensive risk models, much of the preschool variance in all three disorders remains unexplained.…”
Section: Sources and Selection Criteriamentioning
confidence: 99%
“…In the present study, children with co-occurring SSD and LI (i.e., those at particular risk of developing reading problems; Peterson et al, 2009), showed frequent omission error pattern use. Foy and Mann (2012) found a significant correlation between omission error pattern use and nonword reading abilities in kindergarten-aged children without SSDs, although the correlation was low (r = -.22). Research is required to determine whether increased omission and atypical error pattern use in younger children with SSD (i.e., younger than 3 years old) is predictive of later reading problems.…”
Section: Limitations and Future Directionsmentioning
confidence: 79%
“…These patterns may aid in the early identification of children who are at risk of developing co-occurring SSD and LI and also, therefore, later reading problems. For example, Foy and Mann (2012) found that omission error pattern use at the beginning of kindergarten was significantly correlated with nonword reading at the end of the year in children with typical development. Although speech-language impairments often remain undiagnosed in preschool children (Tomblin et al, 1997), surface speech behavior associated with a linguistic deficit may be relatively easy to identify by parents, teachers, and SLPs at a young age.…”
Section: Error Patternsmentioning
confidence: 99%
“…Notably, these phonological deficits are reported to largely persist into adulthood (Shaywitz et al, 1999;Wilson & Lesaux, 2001). To date, research on phonological abilities in DD has focused predominantly on either speech perception (e.g., Ziegler, PechGeorgel, George, & Lorenzi, 2009) or production (e.g., Foy & Mann, 2012). Current models of speech production, however, suggest that the interaction between speech perception and production might be crucial in understanding the development of phonological representations (Guenther, Ghosh, & Tourville, 2006;Hickok, Houde, & Rong, 2011).…”
mentioning
confidence: 99%